2008
DOI: 10.1248/cpb.56.1604
|View full text |Cite
|
Sign up to set email alerts
|

Structures of New Monoterpenes from Thai Herbal Medicine Curcuma comosa

Abstract: Three new monoterpenes, comosoxide A (1), comosoxide B (2), and comososide (3), were isolated from the methanolic extract of the rhizomes of Curcuma comosa cultivated in Thailand. Their structures were elucidated on the basis of chemical and physicochemical evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…The pericarp of the fruit contains considerable amounts of biologically active compounds, such as xanthones, terpenes, anthocyanins, tannins, and phenols. For centuries, the pericarp of mangosteen was used as a medicinal agent by Southeast Asians in the treatment of skin infections and wounds, amoebic dysentery, diarrhea, and cholera [912]. Recently, commercial products of mangosteen added with essential minerals, containing mangosteen, green tea ( Camellia sinensis ), aloe vera, and multivitamins, were used by cancer patients as a dietary supplement [13].…”
Section: Introductionmentioning
confidence: 99%
“…The pericarp of the fruit contains considerable amounts of biologically active compounds, such as xanthones, terpenes, anthocyanins, tannins, and phenols. For centuries, the pericarp of mangosteen was used as a medicinal agent by Southeast Asians in the treatment of skin infections and wounds, amoebic dysentery, diarrhea, and cholera [912]. Recently, commercial products of mangosteen added with essential minerals, containing mangosteen, green tea ( Camellia sinensis ), aloe vera, and multivitamins, were used by cancer patients as a dietary supplement [13].…”
Section: Introductionmentioning
confidence: 99%
“…These latter groups of metabolites are often of more interest for use in traditional medicine (Kennedy and Wightman, 2011). After quenching, samples are extracted, which typically involves a wide range of organic or inorganic solvents such as, methanol (Kanchanapoom et al, 2001; Nakamura et al, 2008; Sawasdee et al, 2009; Tripatara et al, 2012; Padumanonda et al, 2014), ethanol (Sutthanut et al, 2007; Thiengsusuk et al, 2013), ethyl acetate (Shimokawa et al, 2013), or hexane (Lu et al, 2009) depending upon the metabolites of interest. There are numerous extraction methods available, e.g., classical solvent extraction, steam extraction, supercritical fluids extraction, microwave-assisted extraction, subcritical water extraction or high hydrostatic pressure extraction (Starmans and Nijhuis, 1996; Stalikas, 2007; Zhang et al, 2011; Khoddami et al, 2013; Khoomrung et al, 2013).…”
Section: Metabolomicsmentioning
confidence: 99%
“…In the course of our studies on bioactive constituents from Zingiberaceae plant, [1][2][3][4][5][6][7][8][9][10][11][12] we previously reported that the methanolic extract from the rhizomes of Zingiber (Z.) cassumunar showed inhibitory effects on lipopolysaccharide (LPS)-induced nitric oxide (NO) production in mouse peritoneal macrophages.…”
mentioning
confidence: 99%
“…As a continuing study, the methanolic extract and its EtOAc-soluble fraction from the rhizomes of Z. cassumunar were found to inhibit invasion of human fibrosarcoma HT 1080 cells through Matrigel-coated filters in vitro. Eight new phenylbutanoids designated cassumunols A (1), B (2), C (3), D (4), E (5), F (6), G (7), and H (8) were isolated from the EtOAc-soluble fraction together with 30 known constituetns. This paper deals with the structure elucidation of new phenylbutanoids (1)(2)(3)(4)(5)(6)(7)(8) and the inhibitory effects of principle constituents on invasion of HT 1080 cells (Chart 1).…”
mentioning
confidence: 99%